2010
DOI: 10.1210/jc.2009-2421
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the KISS1 Gene in Disorders of Puberty

Abstract: Two KISS1 mutations were identified in unrelated patients with idiopathic CPP. The p.P74S variant was associated with higher kisspeptin resistance to degradation in comparison with the wild type, suggesting a role for this mutation in the precocious puberty phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
178
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(191 citation statements)
references
References 20 publications
1
178
0
12
Order By: Relevance
“…Mutations or SNPs associated with CPP were initially described in KISS1 and KISS1R (7,8,9), but mutations of these genes are very rare in sporadic cases of iCPP (10). A recent whole-exome sequencing study identified mutations in the makorin RING finger 3 (MKRN3) gene in 15 individuals with iCPP (11).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations or SNPs associated with CPP were initially described in KISS1 and KISS1R (7,8,9), but mutations of these genes are very rare in sporadic cases of iCPP (10). A recent whole-exome sequencing study identified mutations in the makorin RING finger 3 (MKRN3) gene in 15 individuals with iCPP (11).…”
Section: Introductionmentioning
confidence: 99%
“…Autosomal-dominant mutations leading to enhanced biological activity are found in a variety of disorders, including Noonan syndrome (in the MAPK pathway) (15)(16)(17), testotoxicosis (in the LH receptor) (18) and in central precocious puberty (in the ligand for GPR54, kisspeptin) (19). A number of possible mechanisms for this putative increased leptin bioactivity can be proposed: the variant may lead to decreased degradation in serum or an altered balance between free and bound circulating leptin with increased free leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Вместе с тем до 75 % мальчиков с ППР имеют визуализируе-мые поражения ЦНС, главным образом гипота-ламические гамартомы [72][73][74][75]. Наследственный вариант ППР отмечается в 20-25 % случаев, что свидетельствует о роли генетических факторов в его этиологии [77,78]. В 2008 году была от-мечена роль кисспептинового сигнального пути в патогенезе ППР.…”
Section: особенности регуляции активности кисспептина при преждевремеunclassified
“…Несомненно, сам KISS1 является еще одним очевидным кандидатным геном для объяснения механизмов преждевременного полового созревания. Редкий вариант мутации гена кисспептина, р.P74S, был выявлен у ребен-ка со спорадическим ППР [78]. Мутация р.P74S в гетерозиготном состоянии была выявлена у мальчика, у которого появилось ППР в го-довалом возрасте с очень высокими уровнями базального ЛГ и тестостерона [78].…”
Section: особенности регуляции активности кисспептина при преждевремеunclassified
See 1 more Smart Citation